Kaffee Kostuum : a dilemma in retail financials - Boute, Robert N.; Van Mieghem, Jan A. (London : Kellogg School of Management, 2020)
Kaffee Kostuum is a short case that introduces inventory and supply chain management and its financial impact. The case provides a simple context for examining basic inventory performance measures to improve operational-as well as financial-performance. The case has three parts: (1) analyzing reordering decisions, leading to the economic order quantity (EOQ) model and corresponding cycle stock levels; (2) investigating the effect of demand uncertainty, leading to the concept of safety stock; (3) and analyzing the impact of various supply-chain redesign initiatives, such as product rationalization, reshoring, and physical centralization, to reduce inventories.
Originally Published InBoute, R. & Mieghem, J. (2020). Kaffee Kostuum: A Dilemma in Retail Financials. 5-120-003. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Inventory control -- Case studies; Business logistics -- Case studies